ЕЛЕКТРОПРОВІДНІСТЬ ТВЕРДИХ РОЗЧИНІВ Pb0,86‑xSmxSn1,14F4+x - Pohorenko, Yuliia; Omel’chuk , Anatoliy; Nagornyi , Anton (V.I.Vernadsky Institute of General and Inorganic Chemistry, 2021)
In the PbF2 – SmF3 – SnF2 system, heterovalent substitution solid solutions Pb0.86-xSmxSn1,14F4+x (0 < x ≤ 0.15) with the structure β-PbSnF4 are formed. The unit cell parameters of solid solutions are satisfactorily described by Vegard’s rules. The electrical conductivity of the obtained samples decreases in the entire temperature range compared to Pb0.86Sn1.14F4 due to the introduction of SmF3 (at x≤0.08) in the initial structure. It brings them closer to the values of the electrical conductivity of β-PbSnF4. However, at temperatures above 520 K, the electrical conductivity of solid solutions is almost twice higher than that of the initial phase Pb0.86Sn1.14F4 (σ553 = 0.054 and 0.023 S/cm, respectively). The electrical conductivity of solid solutions increases with the Sm3+ content, reaching maximum values at x = 0.1. The Pb0.76Sm0.10Sn1.14F4.10 phases have the highest electrical conductivity and the lowest activation energy (σ373 = 1.08 • 10-2 S/cm). The substitution of Pb2+ ions by Sm3+ ions in the fluoride-conducting phase Pb0,86Sn1,14F4 helps to increase the electrical conductivity by almost an order of magnitude compared to the initial phase and by two orders of magnitude compared to β-PbSnF4. The ionic conductivity activation energy increases in the low-temperature region generally with increasing the SmF3 content and decreases proportionally at temperatures above 430 K. The nature of the dependence of the activation energy on the concentration of the heterovalent substituent and its value indicate that the conductivity of the obtained samples is provided by highly mobile interstitial fluoride ions in the structure of solid solutions. The Hebb-Wagner polarization saturation method was used to determine the electronic conductivity of the samples. It is 2 orders of magnitude lower than the ionic one. The fluorine ion transfer numbers are 0.99 and do not depend on the substituent content.